Solo mio [videorecording (Blu-Ray + DVD)] - Ngiaw, Joy (Angel Studios, 2026)
"A wedding disaster leaves Matt Taylor stranded in Rome--alone, heartbroken, and facing a honeymoon meant for two. Lost in the world's most romantic city, Matt crosses paths with Gia, a warm and determined coffee shop owner who helps him see Rome--and his situation--through a different lens. With her encouragement, and the help of a handful of well-meaning (and wildly meddling) vacationers--Meghan, Julian, Neil, Donna, and Heather--his ruined honeymoon becomes an unexpected adventure. Set against the breathtaking backdrop of Italy, Solo Mio is a heartfelt romantic comedy about resilience, rediscovering joy, and learning that sometimes heartbreak is just the first chapter of a better story."--